Integrated model for predicting the flexural capacity of concrete elements reinforced with non-corrodible discrete reinforcements - Valente, Tiago (2021)
The present work describes an integrated approach that leads to the development of a new model capable of describing the tensile behavior (mode I) of fiber reinforced concrete (FRC), considering the orientation of the fibers, the fibers segregation along the cross-section of the FRC members and the pullout constitutive model of each fiber bridging the two faces of a crack. The possibility of the numerical model to capture the flexural behavior of nonmetallic fiber reinforced concrete members is explored by simulating the response of polypropylene fiber reinforced concrete notched beams submitted to 3-point bending tests.